(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Teenagers face greater risk of pregnancy than the woman in their adulthood. Objective: The purpose of the present study was to see the maternal outcomes of women presented with teenager pregnancy. Methodology: This cross-sectional study was performed in the Department of Obstetrics and Gynecology at Kurmitola General Hospital, Dhaka, Bangladesh for a period of six months from March 2019 to September 2019. The teenage mothers with the age group of 13 to 19 completed years at delivery who were admitted to the Department of Obstetrics and Gynecology were included in this study. On admission, diagnosis was established by history, presenting complaints, physical examination, per-abdominal examination and per-vaginal examination. Complications during pregnancy and labour, mode of delivery, post-partum complications and perinatal outcome were noted. Results: A total number of 100 teenage mothers were recruited for this study. During this study period, 74.0% mothers were aged 18 to 19 years. About 52.0% cases of teenage mothers were suffered from various complications during pregnancy and labor and among them, anemia was in 21.15% cases; UTI was in 3.84% cases; PE was in 17.31% cases; eclampsia was in 3.84% cases; PROM was in 15.38% cases; CPD was in 5.76% cases; prolonged labor was in 93.34% cases; obstructed labor 6.66% cases and preterm labor 15.4% cases. Their modes of delivery were vaginal delivery 63%, caesarean delivery 39%. Among them, indications of caesarean delivery were PROM with Fd 30.77% Gross IUGR with FD 12.82% cases prolonged labor 10.26%, obstructed labor 2.56%, CPD 7.69%, eclampsia 5.13% cases. 57% of teenage mothers suffered from postpartum complications. Among them, PPH was 28.07% cases, inadequate lactation 10.53% cases, Post spinal headache 10.53% cases and wound infection 10.53% cases. Conclusion: In conclusion the most common maternal complication are anemia, UTI, PE, eclampsia, PROM, CPD, prolonged labor, obstructed labor and preterm labor. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):185-188